Hands-On Continuous Integration and Delivery with Jenkins X and Kubernetes - Hohn, Alan (Packt Publishing, 2020)
Build and deliver modern cloud applications-fast! About This Video A rapid way to develop applications for Kubernetes, including Continuous Integration and Continuous Delivery (CI/CD) Work with Jenkins X while building example applications to gain the practical experience you need for your own projects Begin a simple application using Kubernetes and Jenkins X and then enhance it with other great features (such as preview environments) to help you deliver reliable applications-fast In Detail Jenkins X is an exciting and fast way to build applications on Kubernetes. Jenkins X handles the job of configuring Kubernetes to build, test, and deploy your applications, so you can focus on fast delivery and make your applications great! Kubernetes is powerful but complicated; using it not only to run your application but also to build and test it requires a lot of configuration. Jenkins X provides automation for Kubernetes so you can use it to its full potential without spending all of your time configuring and debugging. This course adopts a step-by-step approach to show you how to use Jenkins X, with plenty of hands-on examples that you can use for your own applications. You'll start with a simple example application deployed to Kubernetes using Jenkins X, then build up to awesome features such as preview environments, promotion, and monitoring. With this course, you can learn Jenkins X fast, and immediately apply what you've learned.